Drug-coated balloon in superficial femoral artery in-stent restenosis - Gerardi, Donato; Alfani, Arturo; Tesorio, Tullio; Cioppa, Angelo; Esposito, Giovanni; Stabile, Eugenio (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2018)
The femoropopliteal artery is one of the commonest sites of involvement in peripheral artery disease (PAD) leading to intermittent claudication and/or critical limb ischemia. Endovascular therapy for superficial femoral artery (SFA) disease has been recognized as a safe and efficient therapy and is recommended by current guidelines as the first-line approach. Although the widespread use of new-generation, self-expanding, nitinol stents in SFA stenosis has reduced the shortcomings associated with plain old balloon angioplasty (POBA), lumen renarrowing at the stented (in-stent restenosis – ISR) level still represents a relevant clinical problem, because of higher risk of recurrent ISR, occlusion and surgical revascularization compared to de-novo lesions. In this setting, different treatment options are available and drug-coated balloons (DCBs) have shown good results in terms of safety and effectiveness. In this review we examine the results of different trials exploring the outcome of using DCBs for the treatment of SFA ISR. The available data demonstrate that SFA ISR can be safely treated with percutaneous transluminal angioplasty with a DCB, with a reduction in recurrent restenosis and target lesion revascularization (TLR) at least at 1 year after POBA. The consistent and positive results of different registries and randomized trials support the use of DCB to reduce SFA ISR recurrence.